Clinical features of children with retinoblastoma in Adam Malik Hospital, Medan, Indonesia - Bidasari Lubis (Paediatrica Indonesiana, 2001)
We reviewed patents with retinoblastoma treated at the Department of Child Health, Adam Malik Hospital, Medan from January 1995 to December 1999. Clinical staging was based on Reese-Ellsworth classification (when the disease was limited to the eyeball) or on St Jude Children's Research Hospital (when the disease has extended beyond the eyeball). A total 19 retinoblastoma patients were available, from which 9 were males. Fifteen patients were less than 5 years old, and the average age at diagnosis was 3 years 8 months. In most patients the disease started at the age of less than 5 years, and they presented themselves with advanced stage as usually seen in developing countries. In nine patients the retinoblastoma affected the right eye, 8 affected the left eye, and in 2 patients the tumor was bilateral. The most common presenting symptom on admission was proptosis. Pathological confirmation was obtained in all patients. Bone marrow puncture was done in 15 patients; of whom 13 showed bone marrow metastasis. Since 1998 the standard treatment for patients with proptosis in stage III or IV of the disease was pre-operative chemotherapy followed by enucleation, radiation and chemotherapy.